2002
DOI: 10.1161/01.cir.0000017502.58595.ed
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Xanthine Oxidase Inhibition With Allopurinol on Endothelial Function and Peripheral Blood Flow in Hyperuricemic Patients With Chronic Heart Failure

Abstract: Background-In patients with chronic heart failure (CHF), hyperuricemia is a common finding and is associated with reduced vasodilator capacity and impaired peripheral blood flow. It has been suggested that the causal link of this association is increased xanthine oxidase (XO)-derived oxygen free radical production and endothelial dysfunction. We therefore studied the effects of XO inhibition with allopurinol on endothelial function and peripheral blood flow in CHF patients after intra-arterial infusion and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
376
1
17

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 528 publications
(414 citation statements)
references
References 35 publications
14
376
1
17
Order By: Relevance
“…Diphenylene iodonium (DPI) nonspecifically inhibits flavoprotein-containing enzymes, including NADPH oxidases, NOS, and complex I of mitochondrial electron transport chain [57]. Allopurinol has been reported to inhibit xanthine oxidase-derived oxygen free radical production [58]. Also, rotenone inhibits mitochondrial respiratory chain complex I, specifically, electron transfer within the NADH-Q reductase complex [59].…”
Section: Discussionmentioning
confidence: 99%
“…Diphenylene iodonium (DPI) nonspecifically inhibits flavoprotein-containing enzymes, including NADPH oxidases, NOS, and complex I of mitochondrial electron transport chain [57]. Allopurinol has been reported to inhibit xanthine oxidase-derived oxygen free radical production [58]. Also, rotenone inhibits mitochondrial respiratory chain complex I, specifically, electron transfer within the NADH-Q reductase complex [59].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperuricemic patients exhibit endothelial dysfunction defined as impairment of flow-mediated dilatation of the brachial artery [24]. If hyperuricemic subjects are treated with allopurinol, an improvement in endothelial function has been observed in subjects with chronic heart failure [25]. On the other hand, George et al reported that improvement of endothelial function in heart failure could be achieved with high-dose allopurinol and not probenecid (the latter drug being a uricosuric), suggesting that allopurinol may improve endothelial function via other mechanisms besides lowering uric acid levels, such as by blocking xanthine oxidase-induced oxidants [26].…”
Section: Clinical Evidence For a Role Of Hyperuricemia In Subjects Wimentioning
confidence: 99%
“…[57][58][59][60] Although the mechanism by which uric acid exerts its pathogenetic effect on cardiovascular and cerebrovascular complications is still unclear, high uric acid levels have been shown to induce inflammation, endothelial dysfunction, oxidative metabolism, and platelet adhesion and aggregation. [61][62][63][64][65] All these changes induced by high uric acid levels could conceivably lead to cardiovascular complications and stroke and therefore, drugs that lower uric acid levels have been shown to reverse these changes. [61][62][63][64][65] Losartan, in exception to other ARBs, lowers uric acid levels and its use for the treatment of hypertension has been shown to decrease the incidence of cardiovascular complications and strokes.…”
Section: Aii-mediated Effects Of Arbsmentioning
confidence: 99%
“…[61][62][63][64][65] All these changes induced by high uric acid levels could conceivably lead to cardiovascular complications and stroke and therefore, drugs that lower uric acid levels have been shown to reverse these changes. [61][62][63][64][65] Losartan, in exception to other ARBs, lowers uric acid levels and its use for the treatment of hypertension has been shown to decrease the incidence of cardiovascular complications and strokes. 66,67 In fact, the results from the LIFE study showed that the baseline uric acid level was significantly associated with cardiovascular complications and strokes, especially in women, and that its lowering with losartan accounted for 29% of the reduction of strokes compared to atenolol.…”
Section: Aii-mediated Effects Of Arbsmentioning
confidence: 99%